2005
DOI: 10.1002/macp.200500222
|View full text |Cite
|
Sign up to set email alerts
|

Thermo‐ and pH‐Sensitivities of Thiosemicarbazone‐Incorporated, Fluorescent and Amphiphilic Poly(N‐isopropylacrylamide)

Abstract: Summary: Novel hydrophobic comonomer (p‐methacrylamido)acetophenone thiosemicarbazone was synthesized and polymerized with N‐isopropylacrylamide to get a series of amphiphilic copolymers. The self‐aggregation behavior and thermo‐sensitive character of the (co)polymers were confirmed by TEM observation, fluorescence spectra, and cloud point measurement. Fluorescence emission of copolymer was significantly strengthened or switched off at an excitation wavelength of 320 nm upon the addition of acid or base, respe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 39 publications
1
11
0
Order By: Relevance
“…The triggering of this pH-sensitivity may be attributed to the hydrophilic segments (due to the variation of the amide-water hydrogen bonding), or the hydrophobic segments (due to the protonation/deprotonation of the thiourea group), or both of them. 10 The addition of acid (pH-decrease) significantly increased the amide-water hydrogen bonding, thereby increasing the solvation of polymer chains, which in turn would increase the water solubility of the polymer. This solubilization created conditions for the more convenient hydrophobic association of naphthyl groups in aqueous solutions.…”
Section: Photophysics Of Tercopolymer In Aqueous Solutionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The triggering of this pH-sensitivity may be attributed to the hydrophilic segments (due to the variation of the amide-water hydrogen bonding), or the hydrophobic segments (due to the protonation/deprotonation of the thiourea group), or both of them. 10 The addition of acid (pH-decrease) significantly increased the amide-water hydrogen bonding, thereby increasing the solvation of polymer chains, which in turn would increase the water solubility of the polymer. This solubilization created conditions for the more convenient hydrophobic association of naphthyl groups in aqueous solutions.…”
Section: Photophysics Of Tercopolymer In Aqueous Solutionsmentioning
confidence: 99%
“…7 While the pH values of human body fluids radically change from 0.9 to 1.5 of stomach juice to $8.8 of pancreatic juice, our previous study indicated that the copolymer of (p-methacrylamido)acetophenone thiosemicarbazone and NIPAAm showed a comparatively narrow pH-sensitivity (pH ¼ 6.5-8.5). 10 The pH-sensitive polymers (water-insoluble at low pH, water-soluble at high pH) are of particular interest, because the release rate of the drug can be triggered by the pH of the environment and be used to provide about constant release rates of basic drugs with strongly pH-dependent solubility. 11,12 In this article we report our studies on the effects of a wide range of pH on NIPAAm copolymer properties by fluorescent spectroscopy and transmission electron microscopy.…”
Section: Introductionmentioning
confidence: 99%
“…Generally the naphthyl excimer emission is about 400 nm, but in this case, the excimer emission wavelength of PVP-b-PNT and random polymer is red shifted to 448 nm, which is due to the hydrophobic monomer chemistry structure. Naphthyl thiourea monomer has a tautomeric form, which brings a big conjugated π bond between naphthyl and thiourea residue [22]. The special structure makes higher fluorescence efficiency and reflects the red shift in excimer emssion.…”
Section: The Effect Of Chain Architecture On Photophysicsmentioning
confidence: 99%
“…TSCs and their derivates have also been reported to behave corrosion-inhibiting properties [15][16][17][18]. The thermo sensitivity, pH-sensitivity and pharmacologically versatile TSC groups have been integrated into novel fluorescent and amphiphilic copolymers developing the novel applications of amphiphilic copolymer and environment-responsive materials [19]. Copper potentiometric sensor [20] and the glass carbon electrode modified with nano-␥-Al 2 O 3 [21] containing thiosemicarbazone derivatives were also constructed.…”
Section: Introductionmentioning
confidence: 99%